Social Media, Mediation and the Arab Revolutions - Miriyam Aouragh (tripleC: Communication, Capitalism & Critique)
Abstract: This article discusses the socio-political implications of user-generated applications and platforms through the prism of the Arab revolutions. Popular postmodern conceptualisations such as (post-nation state) network societies, (post-class) immaterial economies and (horizontal) political resistance through multitudes requires rigorous reassessment in the aftermath of the events in the MENA. Although the revolutions have led to a resurgence of debates about the power of new media, such arguments (or rather assertions) are echoes of earlier suggestions related to peculiar fetishisations of ICT in general and social media in particular. The point of my critique is not to deny the social and political usefulness of new media but to examine the pros and cons of the internet. I tackle the juxtaposition of the internet and political activism through the Marxist concept Mediation and investigate how the social, political and cultural realms of capitalism (superstructure) are both conditioned by and react upon the political-economic base. This helps us to understand structural factors such as ICT ownership (political-economic decision making of social media); while deconstructing the effect of cultural hegemony disseminated through mass media. It also overcomes an unfortunate weakness of some “academic Marxism” (an overwhelming focus on theory) by anchoring the theoretical arguments in an anthropological approach